A Novel Gene Coding γ-Aminobutyric Acid Transporter May Improve the Tolerance of Populus euphratica to Adverse Environments - Bai, Xiaotao; Xu, Jianmei; Shao, Xuemin; Luo, Wenchun; Niu, Zhimin; Gao, Chengyu; Wan, Dongshi (Frontiers in Plant Science, 2019)
Novel genes provide important genetic resource for organism innovation. However, the evidence from genetic experiment is limited. In plants, γ-aminobutyric acid (GABA) transporters (GATs) primarily transport GABA and further involve in plant growth, development and response to various stresses. In this study, we have identified the GATs family in Populus species, and characterized their functional evolution and divergence in a desert poplar species (Populus euphratica). We found that the GATs underwent genus-specific expansion via multiple whole genome duplications in Populus species. The purifying selection were identified across those GATs evolution and divergence in poplar diversity, except two paralogous PeuGAT2 and PeuGAT3 from P. euphratica. The both genes arose from a tandem duplication event about 49 million years ago, and have experienced strong positive selection, suggesting that the divergence in PeuGAT3 protein function/structure might define gene function better than in expression pattern. Both PeuGAT genes were functionally characterized in Arabidopsis and poplar, respectively. The overexpression of PeuGAT3 increased the thickness of xylem cells walls in both Arabidopsis and poplar, and enhanced the lignin content of xylem tissues and the proline accumulation in poplar leaves, all of which may improve tolerance of salt/drought stress in desert poplars. Our findings help clarify the genetic mechanisms underpinning high tolerance in desert poplars and suggest that PeuGAT3 could be an attractive candidate gene using for engineering trees with improved brown-rot resistance.